Draft Annual Plan 1987-88 Vol-V Government of Tripura - Planning Commission (Planning Commission, 1987)
The Sch. Castes population of Tripura is 3,10,384 (1981 Census) which comprises 15.11% of the total population of the State. the social position of Sch. Castes in Tripura is relatively better than that of their counterparts in other parts of the country. But the production of Sch.Castes in poverty group is much higher in the State. With a view to improving the economical condition and in order to bring them above the poverty line, at per with the level of other communities.
Government of Tripura